Cross My Heart - Fantetti, Eufemia (Italian Canadiana, 2020)
Linked by a series of idiomatic expressions used to describe sadness, loss and love, “Cross My Heart” is a lyric essay delving into the world of journaling bad decisions and broken relationships. A deep and private self appears in diaries; intense curiosity makes resisting the off-limit contents of the confidential accounts difficult for the author. In her search for understanding her place in the life, mind and heart of another, unwanted discoveries ensue. Her father, a constant source of emotional strength and support, offers inadequate advice.